Strategi Pemasaran Produk Coklat Turqiy menurut Etika Bisnis Islam - Ananta Delyana Mafikah; Rika Nur Amelia; Silvi Indah Nurvita Sari; Anugrahi Ziyadatin Ilmi; Hikmatus Sa’diyah; Eny Latifah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research discusses the application of Sharia business ethics in the marketing strategy of Turqiy chocolate products. As a brand committed to Islamic principles, Turqy integrates Sharia ethical values, such as honesty, justice, and transparency, into every aspect of its operations and product promotions. This product marketing strategy is designed to meet the needs of increasingly selective Muslim consumers for halal and high-quality products. This research uses a qualitative approach with descriptive analysis, exploring how Turqiy applies Sharia principles in the packaging, communication, and distribution of its products. The research results show that the application of Sharia business ethics not only enhances consumer trust but also creates a competitive advantage in the global market. This article makes an important contribution to the development of the sharia marketing concept, especially in the food and beverage industry.